Agrobacterium-Mediated High-Efficiency Genetic Transformation and Genome Editing of Chaling Common Wild Rice (Oryza rufipogon Griff.) Using Scutellum Tissue of Embryos in Mature Seeds - Xiang, Zhipan; Chen, Yi; Chen, Yan; Zhang, Lin; Liu, Min; Mao, Dandan; Chen, Liangbi (Frontiers in Plant Science, 2022)
Genetic transformation is an important strategy for revealing gene function, and it is used extensively in both functional genomics study and molecular breeding of rice. Demand on its application in wild Oryza species is rising for their extensive genetic diversity. However, genetic transformation of wild Oryza accessions using calli induced from scutellum tissue of embryos in mature seeds has not been successfully established. In present study, we used Chaling common wild rice (CLCWR) (Oryza rufipogon Griff.) with AA genome to successfully build an Agrobacterium-mediated genetic transformation system based on scutellum tissue of embryos in mature seeds. The calli from CLCWR embryos in mature seeds were easy to be induced and regenerated. The callus induction rate and texture were optimum under 2.5 mg/L 2, 4-D. The optimal hormone combination used for regeneration was 2 mg/L ZT and 0.1 mg/L NAA. Studies on genetic transformation and genome editing showed that the transformation efficiency was 87% ~ 94%, the efficiency of single genome editing and multiplex genome editing are about 60% ~70% and 20% ~ 40%, respectively. Compared with Nipponbare, CLCWR had higher Hyg-resistant callus frequency and transformation efficiency. Taken together, our study provides a material resource and an established highly efficient transformation system for the genetic transformation for common wild rice.